Mortality among benzene-exposed workers in China. - Hayes, R B (1996)
A large cohort of 74,828 benzene-exposed and 35,805 nonexposed workers employed between 1972 and 1987 in 12 cities in China was followed to determine mortality from all causes. Benzene-exposed study subjects were employed in a variety of occupations including coating applications, and rubber, chemical, and shoe production. Mortality was slightly increased among workers with greater cumulative exposure to benzene (ptrend < 0.05), but this excess was largely due to cancer deaths (ptrend < 0.01). Deaths due to lymphatic and hematopoietic malignancies (ptrend = 0.01) and lung cancer (ptrend = 0.01) increased with increasing cumulative exposure to benzene. Investigations continue to relate benzene exposure to specific lymphatic and hematopoietic malignancies and other causes of death.